"We(b)care": How review set balance moderates the appropriate response strategy to negative online reviews. Issue 3 (15th June 2015) - Dens, Nathalie; De Pelsmacker, Patrick; Purnawirawan, Nathalia
Abstract : Purpose: – Consumers often discuss brands and companies online, but no research details how service providers' responses to online reviews influence other readers' perceptions of the reviews and responses. Based on justice theory and the accountability principle, both integrated in equity theory, the purpose of this paper is to examine how service providers should react to different degrees of negative reviews to enhance readers' attitudes, patronage intentions, and intentions to spread positive word of mouth. Design/methodology/approach: – A 3 (review set balance: positive, neutral, negative) × 6 (response strategy) full-factorial between-subjects experiment included 973 respondents. Findings: – More negative balance demands more effort from the service provider to create positive attitudes and encourage behavioural intentions. If a minority of reviewers are dissatisfied, no response is necessary; if the review set is neutral, the service provider should apologize and promise to resolve the problem; if a majority of reviewers are dissatisfied, the most effective response includes both an apology, promise and compensation. These effects are mediated by readers' perceived trust in the response. Word of mouth also requires more effort than favourable attitudes or patronage intentions. Research limitations/implications: – This research reflects the authors' choices with regard to review set balance and managerial responses, which ensure internal validity but may limit external validity. Originality/value: – This study applies offline service recovery strategies to an online review context. It also explicitly incorporates the bystander (potential customer) perspective.